Artificial Intelligence (AI)-Based Premarital Counselling Policy for Strengthening Sakinah Families in Indonesia: An Islamic Family Law Perspective - Hamdi (ANTMIND YOUTH EMPOWER FOUNDATION, 2025)
This article examines the potential of an artificial intelligence (AI)-based premarital counselling policy to strengthen sakinah families in Indonesia from an Islamic family law perspective. High and persistent divorce rates, particularly due to prolonged disputes and economic problems, indicate that existing premarital counselling has not been fully effective in preparing couples for married life. This qualitative, descriptive study with a phenomenological approach explores how AI can be integrated into premarital counselling to anticipate sources of marital conflict and to improve the quality of guidance provided to prospective spouses. Primary data were obtained through in-depth, semi-structured interviews with 47 respondents from diverse regional and professional backgrounds, while secondary data were collected from statistical reports, policy documents, and relevant scholarly literature. Data were analysed using Miles and Huberman’s interactive model, including data condensation, data display, and conclusion drawing. The findings show that AI is perceived as useful for expanding access to counselling services, personalising learning materials, supporting soft-skill and religious education, and providing continuous follow-up before and after marriage. At the same time, respondents emphasise the irreplaceable role of human counsellors in offering empathy, spiritual guidance, and contextual judgement. From the standpoint of Islamic family law and maqāṣid al-sharīʿah, the study recommends the development of a national AI-supported premarital counselling platform, strict data protection and ethical standards, and a hybrid service model that combines AI systems with professional counsellors to support the realisation of sakinah, mawaddah, and raḥmah-based families in Indonesia.